(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2023)
The necessary and obligatory relationship between the legal aspects linked to the regulation of the General State Budgets, with the strategic scope of public procurement is undeniable. This paper precisely analyzes the influence and degree of penetration of the rules of general budgetary discipline in the processing of public procurement files. To develop the proposed analysis, we began by analyzing the purpose of the public budget, as a tool for the fulfillment of the purposes of the State, especially to guarantee the effectiveness of fundamental social rights. It was an essential aspect to study the legal and constitutional principles applicable to budgets, being the principle of budgetary legality, which allowed us to identify the question of limiting public spending, as the fundamental premise on which the rules of budgetary discipline and that condition the legitimate processing of public contracts.